2019
DOI: 10.1007/s40265-019-01083-3
|View full text |Cite|
|
Sign up to set email alerts
|

Triamcinolone Acetonide Extended-Release: A Review in Osteoarthritis Pain of the Knee

Abstract: Triamcinolone acetonide extended-release (ER) 32 mg (Zilretta ® ) is approved in the USA for the management of osteoarthritis (OA) pain of the knee and is administered as a single, 5 mL intra-articular (IA) injection. Although the therapeutic effects from IA corticosteroids are typically short-lived, triamcinolone acetonide ER is formulated in poly (lactic-co-glycolic acid) (PLGA) microspheres that slowly release triamcinolone acetonide in the synovium, enabling their prolonged presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 31 publications
0
64
0
1
Order By: Relevance
“…For instance, an FDA-approved formulation Zilretta Ò utilizes the size properties of microspheres to enable greater retention in the joint and extended release treatment of the active ingredient from within the microsphere for arthritis treatment after intra-articular injection. 49 However, nanomaterials may be more beneficial than micron-sized carriers when utilizing passive targeting strategies. For instance, the smaller sizes of nanomaterials enable them to penetrate barriers in tissues such as the cartilage and localize intracellularly.…”
Section: Drug Delivery Systems That Leverage Charge For Delivery To Tmentioning
confidence: 99%
“…For instance, an FDA-approved formulation Zilretta Ò utilizes the size properties of microspheres to enable greater retention in the joint and extended release treatment of the active ingredient from within the microsphere for arthritis treatment after intra-articular injection. 49 However, nanomaterials may be more beneficial than micron-sized carriers when utilizing passive targeting strategies. For instance, the smaller sizes of nanomaterials enable them to penetrate barriers in tissues such as the cartilage and localize intracellularly.…”
Section: Drug Delivery Systems That Leverage Charge For Delivery To Tmentioning
confidence: 99%
“…These studies have also shown the combination of all three drugs is more effective than any drug alone or pair of two drugs, that TRI MP can confine drug activity to a local area resulting in antigen-specific immunosuppression, and that sustained release of drug from TRI MP is more potent than equivalent unencapsulated doses. Furthermore, injection of microparticles into inflamed joints could be a viable clinical approach as intra-articular injection of corticosteroid containing microparticles is already FDA-approved for osteoarthritis pain management [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…This nested case-control study provides new and novel information on the safety of IACI on the evolution of knee structural changes in OA individuals, a topic of clinical interest in view of previous reports [10][11][12][13][14]27,28 in which controversy still exists regarding possible deleterious effects on joint structure. Data in this study demonstrated that a single IACI in knee OA was safe with no negative impact on articular structural changes, as no differences between the control and IACI groups were found for cartilage volume change, bone curvature, and BML in the evolution of the structural changes post-treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Although several studies have explored the efficacy of IACI to treat knee OA symptoms and the extent and length of response to a single treatment, meta-analysis indicated that the clinical benefit of an IACI after one to six weeks was unclear 8 . Recent clinical trials, however, suggested that repeated treatment with an extended-release formulation of triamcinolone acetonide significantly prolongs and amplifies the symptomatic benefit with no deleterious effect on joint structure when assessed by X-rays 10,11 . In a recent review 12 , it was however, suggested that this particular issue about the safety of IACI remains to be determined until examined more closely.…”
mentioning
confidence: 99%